Política e escolarização em Goiás-Morrinhos na primeira república - Miriam Fabia Alves (2007)
This thesis proposes to discuss the relation between the political elite of Goiás and schooling, with regard to the constitution of a school network and the tensions created through this process. The study confines itself to the state of Goiás during the First Republic and the town of Morrinhos was chosen as an example for the investigation of this relation. Documentary research was supported by a documental corpus, made up of educational legislation, the messages of State presidents, articles from periodicals such as Correio Official, O Democrata, Goyaz and A Informação Goyana as well as documents from schools in Morrinhos, with special emphasis on documentation relating to the Coronel Pedro Nunes School. In Goiás, the period under analysis was characterized by the setting up of the republican regime and also by the appropriation and dissemination of a political culture characterized by the conservative and exclusionary liberalism of the Goiás elites. The schooling process was slow to structure in terms of setting up a network of primary schools, as well as the producing and circulating the basic set of references for the primary school. In the period from 1910 to 1920, the prevailing republican model was an object of dissension among the oligarchies. It was also criticized and contested by different social sectors. Political discourses took up the republican ideals of the formation of a peoples citizenship and restored primary education to the center of the debate. In harmony with this movement, schooling in Goiás underwent a series of transformations, among which were the expansion of the primary school network, the creation of secondary schools, introducing the grade school to the state and the increasing realization of the importance of schooling for the building of a civilized and schooled society.